Academic stress sebagai mediator hubungan antara self-adjustment, self-regulation dan optimism dengan psychological well-being Generasi Z: Academic stress as a mediator of the relationship between self-adjustment, self-regulation and optimism with the psychological well-being of Generation Z - Ananda Humaidah; Rachmat Mulyono (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Studies show that students with low psychological well-being have poor quality relationships with others and are prone to psychological disorders that can affect academic achievement. This study aims to determine the relationship between self-adjustment, self-regulation, and optimism with the psychological well-being of Generation Z students through the mediator of academic stress. This study used a quantitative survey method with 439 Generation Z students in Jakarta, Bogor, Depok, Tangerang, and Bekasi as participants. The sampling technique used quota sampling. Research instrument using the Ryff Psychological Well-being Scale (α = 0.726); self-adjustment scale (α = 0.786); Short version of Self-regulation Questionnaire (α = 0.857); Life Orientation Test Revised (α = 0.554); Academic Stress Inventory (α = 0.926). Data analysis of this study used path analysis using Mplus 7 software. The results showed that only self-adjustment and self-regulation can directly influence psychological well-being. However, academic stress (the mediator) did not significantly affect psychological well-being. This means that academic stress cannot be a mediator in this study. The implication of this research is that universities are expected to improve students' self-adjustment and self-regulation, thereby improving their psychological well-being.